ANALISA KADAR LEMAK PADA ES KRIM YANG DIJUAL DI DAERAH DEMAK BERDASARKAN PERMENKES - Kartikorini, Nastiti (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
ANALISA KADAR LEMAK PADA ES KRIM YANG DIJUAL DI DAERAH DEMAK BERDASARKAN PERMENKESIr. Nastiti K., M.Kes. nastitikartikorini@gmail.com Prodi D3 Analis Kesehatan UM Surabaya AbstractIce cream is a kind of semi-solid food that is made by freezing ice cream flour or a mixture of milk, animal and vegetable fats, sugar, and with or without other foods allowed. Fat can be regarded as the raw material of ice cream. Its function is to give a smooth texture, taste and contribute to a synergistic effect on the extra flavor used. In addition, the use of fat will beautify the apost prandialearance, but at the level of excessive amounts will cause too hard and the results are like sand. Milk fat when consumed in a way and an improper dose (excess consumption), it will give rise to various kinds of diseases. This is because milk fat consists of saturated fats and cholesterol, which can cause a variety of diseases. Contained milk fat content in ice cream has been determined by the government as contained in PERMENKES standat quality ice cream that is 5%. The problems of this research are contained Is fat content in ice cream is in conformity with PERMENKES?. The purpose of this study was to determine fat levels in ice cream based on standard PERMENKES. Descriptive research to determine the fat content in ice cream that is sold in the area Demak. The sample used in this study was the ice cream that is often consumed by people who are sold in stores in the area Demak Surabaya. Criteria ice cream samples are branded or not branded which amounted to 20 samples. Data was collected by laboratory testing fat content in ice cream were examined by the method of extraction, and the data obtained are presented in table form. Techniques of data analysis done by creating conformity percentage of samples based PERMENKES.Based on laboratory tests on 20 samples of ice cream, which is in accordance with the standard sample PERMENKES totaling 9 samples (45%), while that does not meet the standard PERMENKES total of 11 samples (55%). So the ice cream that does not meet the standard PERMENKES more than met the standard of ice cream arrives PERMENKES. Key word : level  fat according to PERMENKES, ice cream,